2015
DOI: 10.2337/dc14-3082
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Linking Glucose Homeostasis and Iron Metabolism Toward the Onset and Progression of Type 2 Diabetes

Abstract: OBJECTIVEThe bidirectional relationship between iron metabolism and glucose homeostasis is increasingly recognized. Several pathways of iron metabolism are modified according to systemic glucose levels, whereas insulin action and secretion are influenced by changes in relative iron excess. We aimed to update the possible influence of iron on insulin action and secretion and vice versa. RESEARCH DESIGN AND METHODSThe mechanisms that link iron metabolism and glucose homeostasis in the main insulin-sensitive tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 67 publications
1
139
0
8
Order By: Relevance
“…For example, oxidative stress from excess iron accumulation can lead to b cell damage and apoptosis and, consequently, contribute to decreased insulin secretion (3). High iron stores in the liver may induce insulin resistance by impairing insulin signaling and by attenuating the liver's ability to extract insulin (4,5). In adipocytes, excess iron can diminish insulininduced glucose transport, whereas in the muscles it may lead to a switch from glucose to fatty acid oxidation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxidative stress from excess iron accumulation can lead to b cell damage and apoptosis and, consequently, contribute to decreased insulin secretion (3). High iron stores in the liver may induce insulin resistance by impairing insulin signaling and by attenuating the liver's ability to extract insulin (4,5). In adipocytes, excess iron can diminish insulininduced glucose transport, whereas in the muscles it may lead to a switch from glucose to fatty acid oxidation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…29 In another line of reasoning, it is suggested that iron depletion allows a more relevant improvement of liver enzyme levels and histological changes present in NAFLD. 6,30 Out of 11 studies evaluated in our review, the only discordant one regarding the interpretation of HPF was that by Chandok et al 3 In the article, HPF was similar in patients with steatosis, NASH or cirrhosis. We speculate whether this finding could be justified by the fact that only 19.3% of the participants in this study were evaluated by liver biopsy and histological analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Favorable effects of phlebotomy on diabetes manifestations suggest that abnormal distribution of normal quantities of body iron contribute to diabetogenesis in some persons without hemochromatosis [143145]. Iron-related dietary, cellular, and molecular mechanisms may contribute to the development or expression of type 2 diabetes [146] (Table 2). These and other mechanisms may also be associated with or cause impaired glucose metabolism, IR, and MetS.…”
Section: Iron In Nonhemochromatosis Diabetesmentioning
confidence: 99%